THE PRACTICE OF MONEY POLITICS IN THE IMPLEMENTATION OF PREFECTIVE ELECTIONS OF ISLAMIC CRIMINAL LAW - Mhd. Teguh Syuhada Lubis (Proceeding International Seminar of Islamic Studies, 2023)
Regarding criminal acts in elections act. Systematically, the criminal provisions in the electoral law are regulated in Book V under the title of Election Crime Book II from Article 488 to Article 554. So that the criminal act of election is regulated in 66 articles. Violations of electoral acts, especially money politics, must then be carried out by law enforcement. Regarding this matter, it can be found in the Fifth Book of Chapter I on Handling Election Crimes – the first part of Article 476 to Article 487 of the Election Law. The essence of the law enforcement process is to refer to Law No. 8 of 1981 concerning the Criminal Procedure Code (KUHAP), unless expressly specified in the Election Law, for example regarding the establishment of an Integrated Law Enforcement Center regulated in Article 486 and Article 487. In other words, in certain cases the Electoral Law is placed as a specificity (lex specialis) of the Criminal Procedure Code as its general provision (lex generalis). As has been stated before that the purpose of the passing down of Shari'a is to achieve benefit and avoid omnipresence on two different dimensions of time, the world and the Hereafter. This means that all aspects of Islamic teachings, must lead to the achievement of these goals, including the economic aspect. Therefore, Islamic Economics must be able to become a pan-acea and a solution to the acute problems of the current economy. The logical consequence is, that to construct an Islamic Economic building it cannot be separated from the Maqashid theory as previously explained. Even Shaikh Muhammad Thahir ibn 'Assyria once said that